Systematic Review: The Effect of Resistance Training on Lipid Profile in Elderly - Huldani, Asnawati, Arini Cahyaning Putri, Laina Sorayya, Aisya Najiha, Muhammad Hasan Ridhoni, San Gunma (Drugs and Cell Therapies in Hematology, 2022)
Background: Coronary heart disease is the number 1 cause of death in the world and mostly occurs in elderly (≥ 60 years). Coronary heart disease mostly caused by dyslipidemia or the abnormality of lipid profiles, namely total cholesterol, LDL, HDL, and triglyceride. WHO recommends elderly to do exercise that prioritizing balance, such as resistance training to prevent the incidence of coronary heart disease. Resistance training is exercise that makes muscles contract using external resistance. Resistance training increases the fat used by muscles, so it can decrease the lipid profile. Purpose: Tosummarized the effect of resistance training on lipid profiles in elderlyby analyzing and comparing relevant researches which are published from 2011-2021. Method: This articleis originally made by searching relevant literatures from databases of medical journals, namely PubMed, Science Direct, and Google Scholar that published in 2011-2021 as many as 4,910 literatures.Those literatures are selected by applying inclusion criteria, namely elderly participants (age≥ 60 years old), using lipid profile as dependent variable, and there is no intervention like special intake and drug during the research. Based on that criteria, there 15 literatures which are analyze in this article. Result: Only 5 literatures show significant enhancement (p < 0.05)of overall lipid profile (total cholesterol, LDL, HDL, and triglyceride), namely progressive resistance training, circuit resistance training, combination of aerobic exercise with circuit resistance training, eccentric training, and water-based resistance training. 1 literature shows no significant enhancement (p > 0.05) of overall lipid profile namely pilates. Insignificant change mostly caused by uncontrolled nutrition intake, inadequate exercise’s frequency and intensity, and measurement mistake. Conclusion: From 15 literatures, that are only 5 literatures that show significant enhancement. Resistance training can help elderly to prevent or recover from coronary heart disease by considering nutritional intake, type, frequency, duration, and intensity of exercise.